1981
DOI: 10.1136/thx.36.4.286
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function abnormalities in Sjogren's syndrome and the sicca complex.

Abstract: The frequency of pulmonary involvement in a group of 20 patients with Sj6gren's syndrome or the sicca complex was evaluated with pulmonary function studies. In 12 patients pulmonary functional abnormalities were demonstrated. The, most common abnormality was airway obstruction. Nine out of 13 patients with the limited variant of the disease (sicca complex) and three out of seven patients with the complete syndrome had abnormal pulmonary function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 14 publications
2
23
0
Order By: Relevance
“…Most of these studies [3,6,8,11] have shown signs of restrictive pulmonary disease in accordance with our previous resuits [1]. Other studies [4,5] have shown signs of obstructive ventilatory disease.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Most of these studies [3,6,8,11] have shown signs of restrictive pulmonary disease in accordance with our previous resuits [1]. Other studies [4,5] have shown signs of obstructive ventilatory disease.…”
Section: Discussionsupporting
confidence: 80%
“…Some authors [3,8,10] have demonstrated the presence of a restrictive lung disease affecting above all the small airways. Segal et al examined 20 patients with SS and concluded that airway obstruction was the most common abnormality [4].…”
Section: Introductionmentioning
confidence: 99%
“…In our patients, in accordance with the studies of Newball and Brahim [2], there is only a moderate restrictive syndrome. On the other hand, the injury of the diffusing ca pacity seems to be, more frequent and im portant, in accordance with what is sug gested by other authors [3,6], demonstrat ing a marked decrease in the interstitial gases exchange. The pathogenesis of this abnormality seems to reside, as suggested by the analysis of the BAL, in a lympho cytic infiltration of the lung's interstitium; there is then constantly present an alveoli tis, even if it is less serious than in other immunological disorders ( fig.…”
Section: Discussionsupporting
confidence: 79%
“…In conclusion, the pulmonary involve ment in SS is: constant and markedly higher than the 60% suggested by other au thors [2,6); unpredictable, indeed we have found no relation between the physiologi cal abnormalities, the BAL and the dura tion of the disease, which is of great clini cal-physiological importance, confirming the respiratory troubles that these patients often complain of [2,3]. At the same time we can say that the BAL seems to be, com pared to the clinical-roentgenographicphysiological analysis, more sensitive in pointing out the pulmonary involvement, and in providing new information for the understanding of the pathogenesis of the disease.…”
Section: Discussionmentioning
confidence: 72%
“…Differences between primary and secondary SS in terms of pulmonary involvement have been described [26,37]. Primary SS patients who are anti-Ro antibody positive often develop more systemic manifestations, with lung disease being commonly reported [6,9,15,29,33]. The most frequent pulmonary abnormalities are interstitial lung disease with interstitial pneumonia (SS-IP) and small airways disease.…”
Section: Introductionmentioning
confidence: 96%